PELATIHAN MEMBANGUN USAHA DIGITAL UNTUK MENUMBUHKAN JIWA ENTERPRENEURSHIP BAGI SISWA SMK MUHAMMADIYAH 2 PEKANBARU - Haris Tri Saputra; Yulisman Yulisman; Akhmad Zulkifli; Uci Rahmalisa (Jubaedah : Jurnal Pengabdian dan Edukasi Sekolah (Indonesian Journal of Community Services and School Education), 2022)
Digital and technology or a tool that is currently almost always there in every aspect of human life that has a goal to help and facilitate work or activities carried out by humans. The impact of digital technology is felt, especially for those who depend on technology for their daily activities. Digital businesses are currently growing and developing very quickly. To build a digital business requires adequate experience and knowledge, and to get this it is enough to take part in training. Training should be carried out early or starting at the school level, especially training for Vocational High School (SMK) students, because SMK students after graduation are targeted to be able to work immediately. The results of this training can be seen from the post-training questionnaire that participants